Transcriptomic analysis of peaches and nectarines reveals alternative mechanism for trichome formation - Chun-Che Huang; Han-Wei Chen; Jo-Wei Allison Hsieh; Yen-Chun Lin; Yi-Pei Li; Chunxian Chen; Yen-Fang Song; Gung-Chian Yin; Te-Lun Mai; Ying-Chung Jimmy Lin; Yuan-Kai Tu (BMC Plant Biology)
Abstract Trichomes in Prunus persica (L.) Batsch are crucial specialized structures that play a protective role against both biotic and abiotic stresses. The fruits with and without trichomes are respectively named as peach and nectarine. At the genetic level, the formation of trichome in peach is controlled by a single gene, PpMYB25, at the G locus. Peach (GG or Gg) is dominant to nectarine (gg), but such regulatory role was reported in a small-scale accession. In this study, we performed large-scale genotype and phenotype screening on 295 accessions. Almost all accessions supported the casual relationship between trichome formation and PpMYB25. However, a peach to nectarine mutant, named Maravilha Nectarine Mutant (MN), was discovered to possess a putative functional PpMYB25 gene sequence (Gg) but revealed nectarine phenotype. Comparative transcriptomic analyses revealed that PpMYB25 transcript was absent in MN. Correlation analyses also demonstrated that the PpMYB25-mediated regulatory network was abolished in MN. In summary, our results demonstrated an alternative mechanism beyond genetic regulation on trichome formation.